Assessment of low altitude aerial data for large scale urban environmental mapping - Hashim, Khairil Afendy (2013)
Development of UAV systems become more popular for missions with high societal impact. Therefore, UAV is developed from the low-altitude photogrammetric mapping to perform the accuracy of the aerial photography and the resolution of the image. The objective of this study is to assess the accuracy of the photogrammetric output i.e. Digital Elevation Model (DEM) and orthophoto. The Ground Control Points (GCPs) and Check Points (CPs) are established using Rapid Static techniques through GPS observation for registration purpose in photogrammetric process. The GCPs is used in the photogrammetric processes to produce photogrammetric output while the CP is employed for accuracy assessment. A Pentax Optio W90 consumer digital camera is also used in image acquisition of the aerial photograph. Besides, this study also involves image processing and map production using Erdas Imagine 8.6 software. The accuracy of the orthophoto is determined using the equation of Root Mean Square Error (RMSE). In a nutshell, UAV system has potential use for largescale urban environmental mapping in field of surveying and other diversified urban environmental applications especially for small area which has limited time and less man power.